Competence, Professionalism, Audit Experience and Auditor's Ability In Detecting Fraud - Agung Prasetyo Nugroho Wicaksono (Jurnal Akademi Akuntansi, 2022)
This study aims to examine the effect of competence, professionalism, and audit experience on the auditor's ability to detect fraud. This type of quantitative research with respondents are inspectors and auditors at the Inspectorate of Batu City. Determination of the number of samples is done by non-probability sampling method with purposive sampling technique. The data in the study used primary data taken directly to the respondents through a given questionnaire. The research data were analyzed using the outer model and inner model tests with the help of the Smart Partial Least Square (PLS) version 3.3.9_64bit software program. The results obtained in this study are competence has a positive and significant effect on the auditor's ability to detect fraud, professionalism has a positive and significant effect on the auditor's ability to detect fraud and audit experience has a positive and insignificant effect on the auditor's ability to detect fraud. Future research is expected to add independent variables from external factors that can affect the auditor's ability to detect fraud such as red flags, workload, and time pressure to obtain valid data.